Integrated transformer using magnetic sheet for LLC resonant converter. Issue 10 (1st May 2014) - Kang, B.G.; Park, C.S.; Chung, S.K.
Abstract : The design and implementation of a simple integrated magnetic (IM) transformer for an LLC resonant converter are presented. The IM transformer with a resonant inductor is implemented using a flexible magnetic sheet. Experimental results are provided to show the validity of the proposed IM transformer.